Advanced medical statistics - Lü, Ying.; Fang, Ji-Qian, 1939- (Singapore ; River Edge, NJ : World Scientific, 2003)
This book presents new and powerful advanced statistical methods that have been used in modern medicine, drug development, and epidemiology. Some of these methods were initially developed for tackling medical problems. All 29 chapters are self-contained. Each chapter represents the new development and future research topics for a medical or statistical branch. For the benefit of readers with different statistical background, each chapter follows a similar style: the explanation of medical challenges, statistical ideas and strategies, statistical methods and techniques, mathematical remarks and.
Ch. 1 History of Statistical Thinking in Medicine / Tar Timothy Chen -- Ch. 2 Evaluation of Diagnostic Test's Accuracy in the Presence of Verification Bias / Xiao-Hua Zhou -- Ch. 3 Statistical Methods for Dependent Data / Feng Chen -- Ch. 4 Statistics used in Quality Control, Quality Assurance, and Quality Improvement in Radiological Studies / Shoujun Zhao / Ying Lu -- Ch. 5 Cost-Effectiveness Analysis and Evidence-Based Medicine / Jianli Li -- Ch. 6 Quality of Life: Issues Concerning Assessment and Analysis / Ji-Qian Fang / Yuantao Hao -- Ch. 7 Meta-Analysis / Zongli Xu / Ying Lu / Chuanhua Yu / Xuyu Zhuo / Ji-Qian Fang -- Ch. 8 Describing Data, Variability and Over-Dispersion in Medical Research / Ming Tan -- Ch. 9 Time Series Analysis And Its Applications in Medical Sciences / Jinxi Zhang / Yingdong Zheng / Dejian Lai -- Ch. 10^
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Medical statistics; Medicine -- Research -- Statistical methods; Médecine -- Recherche -- Méthodes statistiques; MEDICAL -- Research; Medical statistics; Medicine -- Research -- Statistical methods